Heritage under attack: motives for targeting cultural property during armed conflict. Issue 3 (16th March 2017) - Brosché, Johan; Legnér, Mattias; Kreutz, Joakim; Ijla, Akram
Abstract: Although attacks on cultural property have caused international outcry, our understanding of this phenomenon is still limited. In particular, little research has been directed towards exploring the motivations for such attacks. Therefore, we ask: What are the motives for attacking sites, buildings or objects representing cultural heritage? By combining insights from peace and conflict research with findings from heritage studies we present a typology of motivations for attacking cultural property. We identify four, not mutually exclusive, broad groups of motives: (i) attacks related to conflict goals, in which cultural property is targeted because it is connected to the issue the warring parties are fighting over (ii), military - strategic attacks, in which the main motivation is to win tactical advantages in the conflict (iii), signalling attacks, in which cultural property is targeted as a low-risk target that signals the commitment of the aggressor, and (iv) economic incentives where cultural property provides funding for warring parties. Our typology offers a theoretical structure for research about why, when, and by whom, cultural property is targeted. This is not only likely to provide academic benefits, but also to contribute to the development of more effective tools for the protection of cultural property during armed conflict.